Postmodern teleological agents of end in Don DeLilLo's White Noise - Khodadadegan, Neda; Jujar Singh, Hardev Kaur (Canadian Center of Science and Education, 2015)
Apocalyptic literature in its secular form is a rich way of depicting a more meaningful fiction about ateleological end. The aim of postmodern apocalyptic literature is to manifest how the need for structure inspiresthe writers of this genre to use it as a sense-making device in postmodern era. This paper is an analysis ofpostmodern apocalyptic literary concepts in Richard Don DeLillos’ White Noise (1985). The novel represents asense of apocalypticism in a nuclear age when the fear of an atomic ending is not likely to vanish. The presentpaper examines the author’s depiction of the presence of an apocalyptic world in the postmodern setting of theselected text. It also explores the concept of postmodern apocalyptic deity and its imperfect judgment which callsinto question the simplistic depictions of morality. This has been achieved in this study based on a textualanalysis as a methodology by applying Elizabeth K. Rosen’s study of the genre in her book; ApocalypticTransformation: Apocalypse and the Postmodern Imagination (2008). Findings of this study show how theabsence of a complete destruction in the novel manifests the failure of the only sense-making device in the age ofnuclear fear and the everlasting nature of such fears.